Obstacles to the use of social media in teaching Islamic studies in Nigeria from the teachers’ perspective - AbdulMutolib, Aliy Adekunle; Abanami, Fahd AbdulAziz (Journal of Curriculum and Teaching Methodology, 2025)
This study aimed to identify the obstacles to using social media in teaching Islamic studies in Nigeria from the teachers’ perspective. To achieve the study’s objectives, the researchers employed a descriptive survey methodology, with a sample consisting of 42 teachers. A questionnaire was utilized, which included three main areas of obstacles related to the use of social media: obstacles related to teachers, comprising 7 items; obstacles related to infrastructure and curriculum, comprising 6 items; and obstacles related to students and the home environment, comprising 8 items. The current results revealed that the most significant obstacles were those related to students and the home environment, with teachers’ assessments of these obstacles being rated highly. Additionally, no statistically significant differences were found in the responses based on gender or years of experience. In light of these findings, the study presented several recommendations, the most notable of which include the necessity of enhancing the technological infrastructure in schools, which involves providing internet services for students and teachers, along with technical support to create suitable conditions for using social media in teaching Islamic studies in Nigeria.